Factors facilitating completion of mainstream education in an ordinary school : reflections of young adults with cerebral palsy - Luger, Rosemary Jean (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil (Rehabilitation))--Stellenbosch University, 2016.